Diffusion of inositol 1,4,5-trisphosphate but not Ca2+ is necessary for a class of inositol 1,4,5-trisphosphate-induced Ca2+ waves. - Jafri, M S (1994)
Combining a realistic model of inositol 1,4,5-trisphosphate (IP3)-induced Ca2+ oscillations with the diffusion of IP3 and buffered diffusion of Ca2+, we have found that diffusion of Ca2+ plays only a minor role in a class of agonist-induced Ca2+ wave trains. These waves are primarily kinematic in nature, with variable wavelengths and speeds that depend primarily on the phase differences between oscillators at different spatial points. The period is set by the steady-state value of IP3, while the wave speed approximately equals the wavelength/period. Ca2+ diffusion, which is much slower than that of IP3 because of endogenous buffers, is shown to have only a small effect on the wave trains and not to be necessary for the apparent wave propagation. Diffusion of IP3 sets the phase gradient responsible for these wave trains, which consist primarily of localized cycles of Ca2+ uptake and release. Our results imply a possible previously undisclosed role for IP3 in cell signaling.